2015
DOI: 10.1002/etc.3236
|View full text |Cite
|
Sign up to set email alerts
|

Predicted and observed therapeutic dose exceedances of ionizable pharmaceuticals in fish plasma from urban coastal systems

Abstract: Instream flows of the rapidly urbanizing watersheds and estuaries of the Gulf of Mexico in Texas (USA) are increasingly dominated by reclaimed waters. Though ionizable pharmaceuticals have received increasing attention in freshwaters, many research questions remain unanswered, particularly in tidally influenced urban coastal systems, which experience significant spatiotemporal variability in pH that influences bioavailability and bioaccumulation. The authors coupled fish plasma modeling of therapeutic hazard v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 70 publications
1
33
2
2
Order By: Relevance
“…Though the scope of surface water sampling in the present study was limited to 1 season and we did not attempt to quantify effluent dilution in this tidally influenced bayou, similar levels of sucralose were observed in surface water and effluent, which had similar salinities, relative to bottom waters characterized by markedly elevated salinity, while caffeine levels in surface water were an order of magnitude lower than in the effluent discharge (Table 1). A related study by our team observed similar patterns between surface and bottom observations and salinity across seasons in Buffalo Bayou and several other tidally influenced urban estuaries of Texas [11]. Future studies are necessary to understand tidal influences on exposure and risks of pharmaceuticals and other consumer products in such hydrologically dynamic systems.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Though the scope of surface water sampling in the present study was limited to 1 season and we did not attempt to quantify effluent dilution in this tidally influenced bayou, similar levels of sucralose were observed in surface water and effluent, which had similar salinities, relative to bottom waters characterized by markedly elevated salinity, while caffeine levels in surface water were an order of magnitude lower than in the effluent discharge (Table 1). A related study by our team observed similar patterns between surface and bottom observations and salinity across seasons in Buffalo Bayou and several other tidally influenced urban estuaries of Texas [11]. Future studies are necessary to understand tidal influences on exposure and risks of pharmaceuticals and other consumer products in such hydrologically dynamic systems.…”
Section: Resultssupporting
confidence: 56%
“…Based on our previous observations of salinity differences with depth in Buffalo Bayou [11], samples of effluent, surface water (0.3 m from surface), and bottom water (0.3 m from sediment-water interface) and biological samples were collected during an extensive sampling event on 15 September 2013. Sample collection followed Texas Commission on Environmental Quality methods by boat electrofishing, minnow trapping, and cast netting for 14 fish species, including Lepisosteus oculatus (spotted gar; family Lepisosteidae), Micropterus salmoides (largemouth bass; family Centrarchidae), Lepomis megalotis (longear sunfish; family Centrarchidae), Dorosoma cepedianum (gizzard shad; family Clupeidae), Menidia beryllina (inland silverside; family Atherinopsidae), Hypostomus plecostomus (armored catfish; family Loricariidae), Ictiobus bubalus (smallmouth buffalo; family Catostomidae), Ictalurus punctatus (channel catfish; family Ictaluridae), Mugil curema (white mullet; family Mugilidae), Mugil cephalus (striped mullet; family Mugilidae), Dormitator maculatus (fat sleeper; family Eleotridae), Brevoortia patronus (Atlantic menhaden; family Clupeidae), Micropogonias undulatus (Atlantic croaker; family Sciaenidae), and Fundulus grandis (gulf killifish; family Fundulidae).…”
Section: Field Samplingmentioning
confidence: 99%
“…In some cases predicted values were far less than those observed for fish collected in the field. Du et al (2014) found higher than predicted plasma concentrations for diphenhydramine and carbamazepine in field-collected Longear sunfish ( Lepomis megalotis ), which was also noted by Scott et al (2016) for diphenhydramine and diltiazem in several species of fish.…”
Section: Introductionmentioning
confidence: 67%
“…Tanoue et al (2015) noted that field-based values for BAF plasma (measured plasma / ambient water) were several times higher than those for a predicted water-only BCF plasma value, which were obtained with modeled values (equation 2 above) based on ambient water concentrations indicating that bioaccumulation of these compounds is generally higher than predictions based on water-only exposure. Other studies have observed plasma concentrations that are higher than those predicted using basic bioaccumulation equations with log D ow and water concentrations (Du et al 2014; Scott et al 2016) indicating that aqueous uptake may underestimate the amount bioaccumulated in the environment. The data of Du et al (2014) indicated that concentrations for many of these pharmaceuticals were substantially higher in invertebrates as compared to fish, sometimes by an order of magnitude.…”
Section: Discussionmentioning
confidence: 89%
“…Notable exceptions for U.S. waters include the analysis of CECs in effluent and marine waters in southern California (Vidal-Dorsch et al, 2012) and Charleston Harbor (Hedgespeth et al, 2012), receiving waters in four estuaries along the Texas coast (Scott et al, 2015), San Francisco Bay (Klosterhaus et al, 2013), and Lubliner et al, (2010) who reported on effluent concentrations from WWTPs in Puget Sound, Washington. As far as we know, there are no studies that tested for a large suite of CECs in whole-body fish in marine waters.…”
Section: Introductionmentioning
confidence: 99%